The impact of profitability on capital structure and speed of adjustment: empirical study on selected ASEAN countries - Amin, Sahar (2019)
Capital structure theory has been discussed since Modigliani and Miller in 1958. The paper attempts to investigate the relationship between profitability and leverage in the selected ASEAN countries and the pace at which the firms in these countries converge to target capital structure. The sample consists of the manufacturing industries of Malaysia, Singapore, Thailand, Indonesia, Philippines and Vietnam. ASEAN is one of the emerging economies and is expected to be 4th largest by 2050. The paper examine the relationship of profitability and leverage by employing various indicators of profitability such as Return on Assets, Return on Equity, Net profit Margin and Operating profit margin. Furthermore, first difference GMM is applied to estimate the adjustment speed. The findings revealed that pecking order theory dominate the ASEAN region exhibiting that firms prefer internal financing. The paper also showed evidence of the firms adjusting to the target except the firms in Singapore.